Perjanjian Kemitraan Antara PT. Go-Jek Indonesia Cabang Bali Dengan Driver Online Yang Tidak Memenuhi Asas Keseimbangan - Kadek Gustama Prabawita; Dewa Gede Pradnya Yustiawan (Jurnal Hukum dan Sosial Politik, 2023)
In the partnership agreement between PT. GO-JEK Indonesia with online motorcycle taxi drivers does not meet the principle of balance. The principle of balance which is intended to harmonize legal institutions in agreements known in civil law which has the aim of making the agreement equal or balanced. This study aims to determine the legal consequences of not fulfilling the principle of balance in the partnership agreement between PT. GO-JEK Indonesia Bali Branch With Online Ojek Drivers. As discussed in this study are the legal consequences and legal protection of agreements that do not meet the principle of balance in the partnership agreement between PT. GO-JEK Indonesia Bali Branch with online motorcycle taxi drivers. The research method in this study is a normative research method, which is a legal research library by reviewing regulations and theories of experts related to the problems discussed. After doing the research, it was concluded that the result of the partnership agreement between PT. GO-JEK Indonesia Bali Branch with online motorcycle taxi drivers creates an imbalance between the rights and obligations of the parties. And GO-JEK in resolving problems that cannot be carried out through deliberation is allowed to take legal action by bringing the dispute to a court that has been determined by GO-JEK, namely the South Jakarta Court, but with the determination of the Court by GO-JEK, it can be difficult for partners who live outside city or far from the Court.